Vicinal dianion of triethyl ethanetricarboxylate: Syntheses of (±)-lichesterinic acid, (±)-phaseolinic acid, (±)-nephromopsinic acid, (±)-rocellaric acid, and (±)-dihydroprotolichesterinic acid - Manat Pohmakotr (2018)
The vicinal dianion 2 derived from triethyl ethanetricarboxylate reacted regioselectively with aldehydes and ketones at C(β) to provide paraconic acid derivatives 5a-f in moderate to high yields as mixtures of diastereoisomers. The paraconic acid derivatives 5e and 5f were utilized as the starting materials for the syntheses of (±)-lichesterinic acid (12), (±)-phaseolinic acid (13), (±)-nephromopsinic acid (14), (±)-rocellaric acid (15), and (±)-dihydroprotolichesterinic acid (16).